Identification of organic phosphorus covalently bound to collagen and non-collagenous proteins of chicken-bone matrix. The presence of O-phosphoserine and O-phosphothreonine in non-collagenous proteins, and their absence from phosphorylated collagen - Cohen-Solal, Lola (1979)
Non-collagenous phosphoproteins, almost all of which can be extracted in EDTA at neutral pH in the presence of proteinase inhibitors, are identified in the matrix of chicken bone, and are therefore not covalently bound to collagen. Similarly, all the peptides containing γ-carboxyglutamic acid are present in the EDTA extract and none in the insoluble residue, confirming that none is covalently linked to chicken bone collagen. However, organic phosphorus is also found to be present in chicken bone collagen, principally in the α2-chains. Of the total protein-bound organic phosphorus present in chicken bone matrix, approx. 80% is associated with the non-collagenous proteins and 20% with collagen. The soluble non-collagenous proteins contain both O-phosphoserine and O-phosphothreonine and these account for essentially of their organic phosphorus content. In contrast, collagen contains neither O-phosphoserine nor O-phosphothreonine. Indeed, no phosphorylated hydroxy amino acid, phosphoamidated amino acid or phosphorylated sugar could be identified in purified components of collagen, which contain approximately four to five atoms of organic phosphorus per molecule of collagen. Peptides containing organic phosphorus were isolated from partial acid hydrolysates and enzymic digests of purified collagen components, which contain an as-yet-unidentified cationic amino acid. These data, the very high concentrations of glutamic acid in the phosphorylated peptides, and the pH-stability of the organic phosphorus moiety in intact collagen chains strongly suggest that at least part of the organic phosphorus in collagen is present as phosphorylated glutamic acid. This would indicate that the two major chemically different protein fractions in chicken bone matrix that contain organic phosphorus may represent two distinct metabolic pools of organic phosphorus under separate biological control.